Preparing Al2O3/TiO2 nano-multilayers on the surface of FeAl/Al2O3 coating as tritium permeation barrier - Enkai Guo; Yifu He; Fen Zhong; Bowen Fu; Kun Wang; Guangxu Cai; Changzhong Jiang; Feng Ren (Nuclear Fusion)
Preparing tritium permeation barrier (TPB) coating on the surface of structural materials can effectively alleviate tritium permeation in fusion reactor system. However, due to the existence of inevitable certain number of defects in TPB, there is still a gap between the commonly prepared TPB coatings and the requirements proposed by fusion reactors. In this work, composite coatings with Al _2 O _3 /TiO _2 nano-multilayers (NMLs) covering on the surface of FeAl/Al _2 O _3 coating were prepared as TPB. The FeAl/Al _2 O _3 TPB coating on the surface of 316L stainless steel was prepared by electrochemical deposition of Al, aluminization and in-situ oxidation. Due to the aggregation of Cr, there are micro sized defects in the Al _2 O _3 layer. The presence of defects seriously reduces its hydrogen isotopes permeation resistance. The atomic layer deposition was then adopted to prepare Al _2 O _3 /TiO _2 NMLs with period thickness of 15, 7.5 and 3 nm on the surface of Al _2 O _3 layer, which not only cover the defects, but also utilize interfaces to suppress hydrogen isotopes permeation. The composite coating sample with the period thickness of 3 nm showed great enhancement of two orders of magnitude in deuterium permeation resistance property compared to the original FeAl/Al _2 O _3 TPB coating at 500 °C, and the permeation reduction factor reaches a high value of 5 × 10 ^5 , which far above the requirements of future fusion reactors.